In Vitro and In Vivo Studies of Oral Thin Films Containing Bisoprolol Fumarate - Panati, Dinakar; Varalakshmi, C.; Prakash Reddy, P.K.; Pamula Reddy, B. (Asian Journal of Chemistry, 2011)
The aim of the study is to prepare oral thin films (OTF) containing bisoprolol fumarate and to evaluate their dissolution and pharmacokinetic behaviour. Oral thin films were prepared using core polymers hydroxypropyl methylcellulose, kollicoat SR 30 D and poly(vinyl alcohol). Both the films were characterized by content uniformity, disintegration and in vitro dissolution studies to compare their release behaviours. Both the films showed a rapid disintegration property that was > 1 min after insertion into the medium. The formulations have good cumulative percentage drug release suitable for both immediate and controlled release. The oral thin films have excellent stability for a period of 8 weeks. The pharmacokinetic results suggest that oral thin films containing bisoprolol fumarate have potential use, in controlling hypertension and also in the treatment of cardiac diseases in geriatric patients, as an alternative to the present formulations in the market with better patient compliance.